KARYA ROH KUDUS YANG KARISMATIS DALAM KISAH PARA RASUL - Stevanus, Kalis (Shift Key : Jurnal Teologi dan Pelayanan, 2021)
Pentecostals always interpret the activity of the Holy Spirit in the Acts of the Apostles based on the phenomena recorded by Luke as describing the charismatic acts of God, namely anointing and empowering believers for evangelistic activities and divine service. This article specifically discusses the work of the Spirit of God from the perspective of the book of Acts. The research method used is a qualitative method with a literature review approach, namely analyzing various scientific literatures and books related to the subject, and then the results are presented descriptively. Based on a comprehensive investigation of the Acts of the Apostles narrative, it is concluded that Luke focuses more on the activity of the charismatic Spirit of God as a tool or power for effective testimony and ministry, not soteriology. This charismatic activity of the Spirit of God is not only experiential, but also functional to fulfill the vocation of evangelism and ministry.